Chemical constituents and nitric oxide inhibitory activity of supercritical carbon dioxide extracts from Mitragyna speciosa leaves - Tohar, Norsita; Shilpi, Jamil A.; Sivasothy, Yasodha; Ahmad, Syahida; Awang, Khalijah (Elsevier, 2019)
Mitragyna speciosa Korth., is a controversial plant that possesses various medicinal values and has been used from time immemorial in folk medicine. Recently, it has been widely abused as a narcotic source. The aim of the present study was to characterize the in vitro nitric oxide (NO) inhibition property of the supercritical CO 2 fluid extracts from M. speciosa leaves and to identify the chemical constituents of the extract that exhibited the most inhibition without toxicity effect. Samples were extracted using the green technology, supercritical fluid extraction (SFE) technique via CO 2 as the mobile phase. The NO inhibitory activity was evaluated by Griess assay, which measures the formation of nitrite ion (NO 2 − ) in recombinant mouse interferon gamma/lipopolysaccharide (IFN-γ/LPS) stimulated RAW 264.7 cells. Matrix 5 Step-1 (M5S1) that was extracted with pure CO 2 at 3000 psi and 60 °C exhibited the highest NO inhibitory activity (60.08%) without cytotoxicity (cell viability, 91.98%) at a concentration of 100 μg/mL. GC and GC–MS analysis revealed palmitic acid as the major constituent (34.90%) of M5S1. This study provides first evidence that M5S1, the non-alkaloidal extract obtained by supercritical fluid extraction of M. speciosa leaves possesses potential property in preventing inflammatory diseases mediated by excessive production of NO. © 2016 The Authors